2017
DOI: 10.1038/s41598-017-17645-y
|View full text |Cite
|
Sign up to set email alerts
|

Silica inhalation altered telomere length and gene expression of telomere regulatory proteins in lung tissue of rats

Abstract: Exposure to silica can cause lung fibrosis and cancer. Identification of molecular targets is important for the intervention and/or prevention of silica-induced lung diseases. Telomeres consist of tandem repeats of DNA sequences at the end of chromosomes, preventing chromosomal fusion and degradation. Regulator of telomere length-1 (RTEL1) and telomerase reverse transcriptase (TERT), genes involved in telomere regulation and function, play important roles in maintaining telomere integrity and length. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The current study further corroborates the findings of our previous study in which we identified telomere instability as observed by significant increases in telomere length and TERT expression at 4 and 32 wk after 15 mg/m 3 of silica × 6 h/d × 5 d exposure 55 . Here, we provide the first experimental evidence that DNA damage-induced shelterin dysfunction after silica exposure could allow for the development of pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study further corroborates the findings of our previous study in which we identified telomere instability as observed by significant increases in telomere length and TERT expression at 4 and 32 wk after 15 mg/m 3 of silica × 6 h/d × 5 d exposure 55 . Here, we provide the first experimental evidence that DNA damage-induced shelterin dysfunction after silica exposure could allow for the development of pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…RTEL1 is transiently associated with telomeres and is involved in the maintenance of T-Loop structure of telomeres by unwinding telomeric G4 DNA and allowing efficient telomere replication and stability. Its deletion or reduction could result in the loss of T-Loop structure 55,57 . Similar to our previous findings using an acute 5-d silica exposure regimen 55 , we observed significant decreases in RTEL1 expression in lung tissue of rats at 16 hr after 3, 6, and 12 wk of silica exposure compared to air control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations